Integration of Digitally-Assisted Assessment in the EFL Classroom - Tazhibayeva, E.R.; Köksal, D.; Dolidze, T.; Ulum, O.G. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The global landscape of higher education has dramatically changed since 2020 due to the pandemic caused by the spread of COVID-19. The pandemic has forced Higher Education Institutions (HEIs) in emergency digitalization at all levels, in teaching and assessment. Through online teaching, the discussions about knowledge protection, cheating, plagiarism resulting from the emergency transition of Distance Learning cannot avoid. It is witnessed the effort taken by the academic and administrative staff of HEIs to timely tackle forcedly changed policies, chanced practices, and the reality in the New Normal. Based on the above-mentioned circumstances; educators from different countries including Kazakhstan, Turkey and Georgia, decided to get united and illustrate through the current study the integration of Digitally Assisted Assessment (DAA) with teaching English as a foreign language (EFL) in these countries. Subsequently, the study has considered the necessity to acquire the opinions from various EFL educators and practitioner teachers locally and globally to develop a qualitative survey seeking responses on the ways how the assessment system has changed in the digital classroom. Also, the type of employed digital tools for successful assessment and how these tools have helped teachers to succeed in digitally assisted assessment. At the same time, the paper aims at identifying the advantages and disadvantages of using DAA in EFL classrooms. Finally based on the survey results will attempt to demonstrate best practices of successful literation of DAA and to provide practical recommendations for future improvement.
Шетел (ағылшын) тілі сабағында цифрлық бағалаудың интеграциясы
Интеграция цифрового оценивания в условиях обучения английскому языку как иностранному
Keywords: higher education; COVID; digitalization; online teaching; distance learning; English as a foreign language; digital tools; assessment.